Elements of discrete mathematics : A computer oriented approach - Liu, Chung Laung; Mohapatra, Durga Prasad (New Delhi: Tata McGraw Hill Education, 2008)
This book, intended for a 3rd/4th Semester course on Discrete Mathematics, presents the subject in an algorithmic point of view without adhering to any particular language. The subject has been treated using concepts and solved examples juxtaposed against each other. Key features A Pseudo code approach to Algorithms Extensive coverage on Algorithm Analysis with one chapter dedicated to this topic Turing Machines, Computability and Formal Languages-topics core to the subject are dealt with comprehensively Online Learning Center, in the face of none provided by major competing titles Pedagogy: Solved Examples: 262 Problems: 694 Programming Exercises: 36 Figures: 230 New to the Edition : Complete and focused coverage of syllabus Better chapter organization: Chapters on Computability and Formal Languages and Finite State Machines clubbed into one. Numerous new topics like Rules of Inference, Warshall's Algorithms, DFS, BFS, Semi-Groups and Monoids added New pedagogical feature in the form of Programming Exercises added under relevant chapters. Over 300 solved and unsolved problems added (189 additional problems and 139 solved problems) An exhaustive OLC in the making Enhanced stress on Propositional Calculus and Discrete Probability New pedagogical feature in the form of programming exercises in the revised edition Various Graph Algorithms such as Kruksal's, Prim,s, and Djikstra's Algorithms have been added Better organization by clubbing two chapters on Automata into one.
Index 545-547p.
Keywords: Discrete mathematics; Mathematics; Sets; Computer Science